Generalized subcutaneous emphysema in a Kangal dog - Karabulut, E.; Durgun, T.; Kom, M. (Indian Veterinary Journal, 2006)
In Veterinary Medicine, bite wounds comprise 10% to 15% of all trauma cases. Most of these injuries involve the head, neck, and/or extremities. in dogs (McKiernan et al., 1984). In this paper a case of generalized subcutaneous emphysema consequent to bite injury in the neck region is reported.